(untitled) (Sciences & Technology. A, exactes sciences, 2013)
In the prebreakdown stage of electrical breakdown of gases under high pressure and high voltage, the space charge field plays an important role. We present in this paper the results of numerical calculations of negative streamer propagation in nitrogen making use of two dimensional Scharfetter and Gummel of zero order scheme which allow us to solve numerically the transport equations under strongly space charge dominated conditions such as occur at the head of propagating streamers. The algorithm is fully two dimensional (three dimensional with cylindrical symmetry) and is proving stable and capable of dealing with the steep density gradients which appear in our calculations. Poisson’s equation is resolved by Biconjugate Gradient Stabilized method. We are interested in using the computer calculations to aid in understanding the notion of streamer. Different sizes of radii of the initial ionized spot are simulated in order to define the role of this parameter on the streamer propagation dynamics.